Political and ethnic views with expressive emotions related in Nalan Xingde's travel notes - Ngiaw, Wai Fun (2012)
Nalan Xingde （1655-1685）, a famous poet and writer from the early Qing Dynasty.In his 10- year career serving as a imperial guard to the Emperor Kangxi, he travelled to the north and south of China, and created about 90 works of travel notes to remember his travels. His travel notes included trips to major cross-provinces, diversified thoughts and contents, as well as outstanding artistic manifestations. This research is sorted according to his work’s creation year and will be discussed in three aspects. Firstly, I explored Nalan’s attitude towards the politics during the era of Emperor Kangxi,especially his views regarding the strategies in handling the country’s border disputes and ethnic groups within the nation and elucidate the reasons why he supported or opposed such policies. Next, I analyzed Nalan’s views and feelings about the birthplace of the Manchu ethnic group, and about the politics, religion and culture in the reign of Emperor Kangxi through the Emperor’s visit to the Taishan Mountain, mausoleum and Buddhist activities. Thirdly, I compared and analyzed the effects of the geographical landscape, which include the natural and cultural landscape on the sentiment of the works of his travel notes. This research which showed Nalan’s travel notes expressed a variety of his state of mind. Through describing Shanhai Pass, Gubeikou and the Mukden, he revealed his pride in the military success of the Qing soldiers. Some of his works from the trip to Southern China also revealed Nalan’s sense of pride in the unification of the country. In his works regarding his mission as an ambassador to the Western regions, Nalan expressed his pride in being an ambassador. Through using monuments and historical figures, Nalan expressed his agreement for the Qing Dynasty’s appeasement policy. He emphasized on the Manchu culture and this reflected that he was a person who never forgot his roots. In his series of work such as in the “Dream of Jiangnan” , Nalan’s mindset was more of a traveller’s view of the natural scenery and cultural landscapes of the South, projecting an image as being completely free and at ease. Nalan’s frontier fortress poems covered a very wide region and those poems reflected the Manchu cultural and customs. In terms of style, due to the influence of geographical environment and sequence, his frontier fortress poems were presented in an uninhibited and plaintive style and much on Nalan’s emotions was felt in these poems.